Total impact of electric vehicle fleet adoption in the logistics industry - Mohammed, Jaby; Villegas, Justin (Frontiers in Sustainability, 2023)
The continental United States heavily relies on land logistics with 3.8 million square miles of land and over 4 million miles of road. Additionally, the United States is committed to achieving the global goal of reaching net-zero emissions by 2050. This article examines the advantages and disadvantages of incorporating electric vehicles (EVs), specifically trucks, into the current logistics industry.This paper also provides a better understanding of what type and magnitude of impact electric trucks' uprising technology have on the logistics industry.